Acute Pulmonary Embolism: Imaging Techniques, Findings, Endovascular Treatment and Differential Diagnoses - Palm, Viktoria; Rengier, Fabian; Rajiah, Prabhakar; Heussel, Claus Peter; Partovi, Sasan (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2020)
Background Acute thrombotic pulmonary embolism (PE) is a common and potentially fatal event with imaging playing a pivotal role in the diagnosis and management of these patients.Method This review discusses imaging techniques, diagnostic algorithms, imaging findings and endovascular treatment of acute thrombotic PE, and illustrates important differential diagnoses relating to the spectrum of acute non-thrombotic PE and non-embolic pulmonary artery disease. The review emphasizes information relevant for everyday radiological practice and highlights recent advances that can be readily applied in the clinical routine.Results/Conclusion Computed tomography pulmonary angiography (CTPA) is the current reference standard for the diagnosis of acute PE. Ventilation and perfusion (VQ) scanning or – in centers with adequate expertise – magnetic resonance imaging (MRI) is indicated in pregnant or young patients and patients with contraindications to iodinated contrast. Invasive angiography is reserved for patients with intended endovascular treatment. Artifacts, acute non-thrombotic PE, chronic PE and non-embolic pulmonary artery diseases should always be considered as differential diagnoses.Key points: Citation Format
Keywords: pulmonary artery; computed tomography angiography; magnetic resonance imaging; digital subtraction angiography; endovascular procedures; pulmonary embolism